Effective blended learning in a higher education pathway programme in South Africa. - Cloete, Roy (My University, 2015)
Physical and electronic resources, tools and environments are increasingly being integrated within mainstream higher education. As institutions seize the potential of technology enablement, blended learning formats have become popular. For the blended learning format to positively impact the quality of education in the institution its effective integration into existing practice is crucial. The Monash South Africa Foundation Programme, a division of Monash University that provides an alternative pathway into higher education, has its focus firmly on delivering quality academic development yet must successfully navigate the challenges of implementing blended learning as part of an institution wide strategic plan for academic excellence. The purpose of this study was to investigate how the perceptions and attitudes of a teacher in the programme towards blended learning echoed the strategic plan of the institution to use the blended learning approach. A qualitative single case study was developed around one teacher, framed by the context of the institution’s strategic education plan and the programme environment, in order to develop a rich narrative of his experience. Multiple methods of data collection were used to allow for results to be triangulated. The study showed that this teacher’s perceptions and attitudes reflected a positive disposition towards the implementation of blended learning but that the perceived barriers placed the individual’s potential of achieving the institutional goals for incorporating blended learning at risk. The need for effective change management and staff that would champion the innovation was identified. An accumulative narrative of teacher experiences was advocated to develop theories to support further effective blended learning in the programme and the institution and thus enable the institution’s strategic goals of achieving academic excellence at ground level.
Keywords: Blended learning; Academic development; Change management; Teacher perception